2021
DOI: 10.1016/j.pathol.2020.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Mecillinam susceptibility in Victorian third generation cephalosporin-nonsusceptible Escherichia coli urinary isolates

Abstract: Please cite this article as: Olenski M et al., Mecillinam susceptibility in Victorian third generation cephalosporin-nonsusceptible Escherichia coli urinary isolates, Pathology,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…A German study investigating resistance to mecillinam in E. coli isolates from urine specimens of adult primary care patients in Germany in 2019/2020 reported that 42 of 46 (91.3%) ESBL-producing isolates (80.4% of samples from female patients) were inhibited by mecillinam [ 30 ]. In an Australian study of urinary specimens with microscopy consistent with UTI, mecillinam susceptibility of E. coli resistant to third-generation cephalosporin was actually marginally higher than that reported for E. coli susceptible to third-generation cephalosporin (87.8% [86/98] vs 83.2% [84/101], respectively) [ 31 ].…”
Section: Literature Search Methodologymentioning
confidence: 99%
“…A German study investigating resistance to mecillinam in E. coli isolates from urine specimens of adult primary care patients in Germany in 2019/2020 reported that 42 of 46 (91.3%) ESBL-producing isolates (80.4% of samples from female patients) were inhibited by mecillinam [ 30 ]. In an Australian study of urinary specimens with microscopy consistent with UTI, mecillinam susceptibility of E. coli resistant to third-generation cephalosporin was actually marginally higher than that reported for E. coli susceptible to third-generation cephalosporin (87.8% [86/98] vs 83.2% [84/101], respectively) [ 31 ].…”
Section: Literature Search Methodologymentioning
confidence: 99%